Analisis Perbandingan Kinerja Keuangan PT. Bank Mandiri Tbk dengan PT. Bank Central Asia Tbk - Shinta Zahira Hayathun Nufus; Aris Munandar; Mukhlis Mukhlis (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
Using the CAMEL method, this study examines the variations in financial performance between Bank Mandiri and BCA Tbk between 2015 and 2024. A comparative quantitative technique was used in this research. The financial statements of both banks were used to gather secondary data. The variables analyzed consist of the Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), Operating Expenses to Operating Income (BOPO), Return on Assets (ROA), and Loan to Deposit Ratio (LDR). Descriptive statistical analysis, the Shapiro-Wilk Normality Test, and the Independent Samples t-Test were used to analyze the data. The research findings indicate that PT Bank Mandiri Tbk and PT Bank Central Asia Tbk exhibit differing financial performance, with significance levels for each variable—CAR, NPL, BOPO, ROA, and LDR—below 0.05. These findings indicate that the two banks have different financial management characteristics and operational strategies in maintaining capital adequacy, credit risk management, operational effectiveness, profitability, and liquidity. It is anticipated that this research will offer further details about the CAMEL approach for assessing bank financial performance for academics, investors, and banking stakeholders.